PERUBAHAN SOSIAL GENERASI MUDA KOMUNITAS PETALANGAN (STUDI PADA SILAT DAN PENGOBATAN DI DESA SUNGAI BULUH KECAMATAN BUNUT KABUPATEN PELALAWAN) - Alsi Alfian; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Desa Sungai Buluh Kecamatan Bunut Kabupaten Pelalawan. The purpose of this study was to analyze the factors that led to changes in social values in the younger generation in Desa Sungai Buluh. Topics focus of this research is the anticipation of traditional values in the younger generation Petalangan the Social Change and Modernization in Desa Sungai Buluh. The sample in this study amounted to 37 people. The author uses descriptive quantitative method and the data were analyzed quantitatively and retrieval using Simple Random Sampling technique. Instruments of data are observation, questionnaires/questionnaire and documentation. From research conducted, the authors found that There are several factors that led to changes in social values Tribe Petalangan younger generation. Namely internal and external factors. Internal factors that influence is change the number of members of the community, the Revolution from within the community. External factors affecting the educational world is Influence, Effect of information and technology, and the Influence of the association. To anticipate that no changes in social values greater then here are efforts being made to control the occurrence of changes in socio-cultural values in the younger generation Petalangan Tribe: Anticipating Social Change Progressively, Anticipation Social Change In Conservative, Moderate In Anticipation of Social Change. Keywords: Changes in Social, Youth, Community Petalangan